Analysis of Cash Flow, Leverage to Earnings Quality as a Moderating Variable on Profitability in Property and Real Estate Companies Listed on the IDX in 2021-2023 - Yuli Kurnia Firdausia; Nilam Aisyah Nurrahma (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze cash flow, leverage on earnings quality as a moderating variable on profitability in property and real estate companies. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the period 2021 to 2023. This study uses a purposive sampling technique with a total of 54 analysis units obtained. The analysis technique used in this study is to use the SPSS 25 application. The results of the study indicate that Cash Flow has no effect on Profitability and leverage has no effect on profitability, while earnings quality has an effect on profitability